Revision of the spider genus Jacaena Thorell, 1897, with descriptions of four new species from Thailand (Araneae: Corinnidae) - Pakawin Dankittipakul (2018)
The spider genus Jacaena Thorell, 1897 is revised on the basis of both somatic and genitalic morphology. Its presumable monophyly is supported by a combined presence of characters. Four new species are described from Thailand: Jacaena lunulata sp. nov., Jacaena punctata sp. nov., Jacaena angoonae sp. nov. and Jacaena peculiaris sp. nov. Four species from Thailand, Laos and China were misplaced in Sesieutes and are here transferred to Jacaena: Jacaena erawan (Deeleman-Reinhold, 2001) comb. nov., Jacaena schwendingeri (Deeleman-Reinhold, 2001) comb. nov., Jacaena thakek (Jäger, 2007) comb. nov. and Jacaena zhui (Zhang and Fu, 2011) comb. nov. New specimens of Jacaena mihun and Jacaena erawan comb. nov. have become available from additional localities other than the type localities. Some specimens originally placed in Sesieutes erawan and Sesieutes schwendingeri belong to J. lunulata sp. nov. and are misplaced and here designated as paratypes of the latter species. The genus currently comprises 10 species occurring in humid rainforests of the Indo-Burmese subregion of the Oriental Region. http://www.zoobank.org/urn:lsid:zoobank.org:pub:97EFA23C-7537-4156-8EF0-2D38CF889F5B. © 2013 Copyright Taylor and Francis Group, LLC.